(untitled) - Harriss-White, Barbara (Cambridge, 2003)
Drawing on her knowledge of the country and on theoretical literature, Barbara Harris-White describes the Indian economy through its most important social structures of accumulation. The book explores a range of topics, including labor, class, the state, gender, religious plurality, caste and space. Harris-White's conclusion adeptly challenges the prevailing belief that liberalization releases the economy from political interference.
Keywords: India,India,Ấn Độ,Ấn Độ; Economic conditions,Economic policy,Điều kiện kinh tế,Chính sách kinh tế; 1947-,1991-